PROPERTI TARI WAKTU DALAM LIPATAN: ANALISIS SEMIOTIKA MELALUI PENDEKATAN CHARLES SANDERS PEIRCE - Sabri Gusmail (Universitas Andalas, 2018)
Waktu Dalam Lipatan is a work of dance that is inspired from the social phenomenon of deadline. Waktu Dalam Lipatan is defined as the activity of multiplying or minimizing the dimensions of an existing form, or can be equated with a time-bound understanding, which means an activity shortens the distance of time by increasing the speed or shortening the duration that already exists. Focusing on the element of attitudes on the psychological individual in a person undergoing a deadline process, related to the utilization of time is not good. In this dance, in addition to the body as the main media of dance, choreographer uses a companion media to strengthen the concept of presentation of works, one of which is a dance property. The dance property becomes part of the body's response in the delivery of these motion patterns. This article will analyze to what extent the existence of a dance property in the work